Living Conditions in Grenada : Poverty and Equity Update - World Bank (World Bank, Washington, DC, 2021)
This poverty and equity report provides updated poverty and inequality statistics from the Grenada Survey of Living Conditions and Household Budget Survey (SLCHBS) conducted between 2018 and 2019 by the Central Statistical Office of Grenada. The SLCHBS 2018–2019 is the third in a series of household surveys. The previous SLCHBS was done in 2008–2009 and is used in this report as a benchmark for trends comparison. The objective of these surveys is to assess the state of living conditions in Grenada, examine poverty and inequality trends, and develop a basket of goods and services that can be used to estimate the Consumer Price Index (CPI) for the country. The survey contains information on household expenditures, housing conditions, demographics, education, health, food security, safety and crime, persons with disabilities, and labor market indicators.